Pemanfaatan Algoritma Floyd Warshall dalam Menentukan Jalur Terpendek Bencana Banjir - Erwadi, Yetman; Handayani, Sri; Saputera, Surya Ade; Fernandez, Sandhy (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Bengkulu Province experienced floods and landslides that caused loss of life and property. These events mainly occur in the Central Bengkulu region and Bengkulu City, caused by damage to the Bengkulu River Watershed (DAS). During the rainy season, the river overflows. In this case the community is also confused when evacuating related to flood disasters, the community is confused in determining which route is the closest for the evacuation route because at the location of the flood disaster there are many routes that can be passed. From the problem the purpose of this research is to create an application that can determine which path is the closest in order to evacuate quickly. From the results of the analysis of this application, it is clear that the implementation of the Floyd-Warshall algorithm in this web application has a very important purpose, namely to assist the community in finding the shortest path to the evacuation point during a flood. The Floyd-Warshall algorithm is known to be effective in finding shortest paths in weighted graphs, as implemented in the context of this application to calculate the shortest distance between every pair of vertices or points within a defined area. The Floyd-Warshall algorithm can only compute shortest paths within areas that are well-defined in terms of vertices and edges, for the test results of the distance obtained in test 1 as far as 0.76 KM, in test 2 as far as 0.40 KM and in test 3 as far as 0.41 KM.